Hardfacing engineering surfaces with Supersonic Laser Deposition of Stellite-6 - LUPOI, ROCCO (My University, 2011)
The capability of manufacturing coatings is of central importance in engineering design. Many components require nowadays the application of additional layers, to enhance mechanical properties and protect against hostile environments. S upersonic Laser Deposition (S LD ) is a novel coating method, based upon Cold Spray (CS) principles. In this technique the deposition velocities can be significantly lower than those require d for effective bonding in CS applications. The additi on of l aser heat energy permits a change in the t hermodynamic experience of impacting particles, thereby offering a greater opportunity for metallurgical bonding at lower velocities compared to the CS process tec hnology. The work reported in this paper demonstrates the ability of the SLD process to deli ver hard facing materials to engineering surfaces. Stelli te - 6 has been deposited on low carbon steel tubes over a range of process parameters, determining the appropriate target power and traverse speeds for coating deposition. Coating properties and param eters were examined to de termine the main properties, micro - structure and processing cost. Their morphology was studied through optical microscopy, SEM and X - Ray D iffr action. The results have shown th at SLD is capable of depositing Stellite - 6, with enhance d properties compared to laser clad counterparts.
International Congress on Applications of Lasers & Electro-Optics (ICALEO)
Keywords: SLD; Cold Spray; supersonic; laser; metal; deposition